Ur III Studies: Bibliography 1997–2014 - Garcia-Ventura, Agnès (Studia Orientalia Electronica, 2015)
Two bibliographical lists of texts from Ur III Mesopotamia (ca. 2112–2004 BC) have been published. The first, compiled by Marcel Sigrist and Tohru Gomi, appeared in 1991 ina volume entitled The Comprehensive Catalogue of Published Ur III Tablets, and included all publications until 1990. The second was published in 1999 by Walther Sallaberger as the final chapter of his work on the Ur III period in the volume Mesopotamien. Akkade-Zeit und Ur III-Zeit (Sallaberger 1999: 351–363). This second list fills in the gaps of the previous one and presents works published until 1997. Since then, no more Ur III bibliographies have been published. Even though today it is much easier to access texts and publications than it was in the past, these lists remain useful nonetheless. In this paper I present an updated list of Ur III publications covering the years 1997–2014. Like Sallaberger 1999, I have also added a few references from the years covered in the previous bibliographical list (in this case, 1994–1997). But unlike the previous lists, the one presented here includes not only publications of tablets and texts, but also studies referring to the Ur III period and the Ur III sources in general. My hope is that the list will be of use both to Assyriologists working with Ur III texts and to scholars interested in the art history and archaeology of the period, as well as those carrying out comparative studies with other periods.